Occupational therapy evaluation for children : a pocket guide - Mulligan, Shelley, ....- (Philadelphia : Lipppincott Williams & Wilkins, 2014)
In pediatrics, occupational therapy practitioners are concerned most with positively impacting the extent to children and their families are able to successfully and meaningfully go about their daily lives, whether it be playing, learning, working, caring for oneself or others, or socializing. Clinical decisions made throughout the evaluation process ultimately shape what and how occupational therapy practitioners deliver interventions, perhaps making the evaluation process the most important and interesting part of the service delivery process. It is the context where we first come know and appreciate our clients, their specific situations, and discover what it is that we, as occupational therapy practitioners can do to be of most help.
Introduction to OT evaluation for children across practice settings -- A guide to evaluation -- Typical child development -- Standardized assessment tools -- Interviewing and conducting observations -- Intervention planning and documentation -- Specialty areas of practice and populations.
Includes bibliographical references and index.
Keywords: Child; Ergotherapie -- Kinderen; Occupational Therapy -- Handbooks